Structural biology of the Gram-negative bacterial conjugation systems. Issue 5 (May 2015) - Ilangovan, Aravindan; Connery, Sarah; Waksman, Gabriel
Highlights Conjugation, a process by which DNA is transported from one bacterium to another, is mediated by type IV secretion systems (T4SSs). T4SSs span the cell envelope and comprise 12 proteins, including 3 ATPases assembling into a ∼4 MDa complex. The plasmid DNA is processed in the cytoplasm by the relaxosome, a complex containing the relaxase protein. The DNA–relaxase complex is recruited to the T4SS, through which it is transported into a recipient cell.